Achieving high energy storage performance and thermal stability concurrently in the cost-cutting Al2O3/Ba0.6Sr0.4Ti0.95Ce0.05O3/ZrO2 composite films for energy storage applications. Issue 6 (15th March 2023) - Ge, Shengyang; Liu, Shuo; Feng, Wuwei; Bao, Zhidi; Liu, Yuqin; Xue, Yuan; Cheng, Bingnan
Abstract: High-performance lead-free dielectric energy storage films have received a lot of attention in the modern electronics industry. In this work, sandwich structured SiO2 /Ba0.6 Sr0.4 Ce0.05 Ti0.95 O3 (BST-Ce)/ZrO2 and Al2 O3 /BST-Ce/ZrO2 composite films were prepared on ITO/glass substrate by a combination of electron beam evaporation and post-annealing. With the introduction of linear dielectric SiO2, Al2 O3, and ZrO2 layers, a high recoverable energy storage density ( W r e c ) of 55.4 J/cm 3 and an efficiency ( η ) of 78% was obtained in SiO2 /BST-Ce/ZrO2 film; an optimal W r e c of 71.5 J/cm 3 and η of 86.1% was obtained in Al2 O3 /BST-Ce/ZrO2 film. Moreover, the sandwich structured multilayers also exhibit an excellent thermal stability, high frequency stability and good fatigue durability. Due to the existence of the electron injection barrier in the interfaces, the schottky emission of the BST film under high electric field and high temperature is effectively suppressed, thereby greatly improving the dielectric breakdown strength. The Al2 O3 /BST-Ce/ZrO2 composite film is promising for the energy storage applications working in the harsh environment of high temperature and high electric field. Our results also show that the sandwich-structured composite film composed of relaxor ferroelectric and linear dielectric layers is an effective method to improve energy storage performance.